1990
DOI: 10.2307/2404310
|View full text |Cite
|
Sign up to set email alerts
|

Transformations of Nitrogen Following the Application of 15 N-Labelled Cattle Urine to an Established Grass Sward

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
1

Year Published

1992
1992
1996
1996

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(28 citation statements)
references
References 29 publications
2
25
1
Order By: Relevance
“…Other studies using urine labelled with 15N-urea have also shown small leaching losses. For example, Fraser et al (1993) recorded a loss of 8% below 1100 mm from an application of urine at a rate of 500 kg N ha -1, while Whitehead and Bristow (1990) measured a loss of 16% below 300 mm from an application rate of 744 kg N ha-1. Thus it seems that a combination of ammonia volatilisation, denitrification, microbial Nimmobilisation and rapid plant uptake may minimise leaching losses in urine patch areas of pasture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies using urine labelled with 15N-urea have also shown small leaching losses. For example, Fraser et al (1993) recorded a loss of 8% below 1100 mm from an application of urine at a rate of 500 kg N ha -1, while Whitehead and Bristow (1990) measured a loss of 16% below 300 mm from an application rate of 744 kg N ha-1. Thus it seems that a combination of ammonia volatilisation, denitrification, microbial Nimmobilisation and rapid plant uptake may minimise leaching losses in urine patch areas of pasture.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have been carried out to determine the fate of these excreted nutrients and these have highlighted the urine patch as an important component of grazed pasture where mobile nutrients like N, S and K are recycled to the soil and plants (e.g. Ryden, 1984;Whitehead and Bristow, 1990;Williams et al, 1990a;Haynes, 1992, 1993a, b). Urine patches are also the major source of nitrate which is leached from grazed pastures (Cuttle et al, 1992;Ryden et al, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…Losses of NH, from urine typically average 20% of the nitrogen content of urine deposited on grassland (Whitehead and Bristow 1990).…”
Section: Emissions From Domestic Animalsmentioning
confidence: 99%
“…Three Table 3). When urine is added to soil, almost all the urea N is converted to the ammoniacal form within a few days (Thomas et a1 1988; Whitehead and Bristow 1990) by the action of urease enzymes, and a substantial proportion of the urinary N, often about IS%, is volatilised as gaseous ammonia within 2-3 weeks (Lockyer and Whitehead 1990). Almost all the volatilised ammonia appears to be derived from the urea component of the urine (Whitehead et al 1989).…”
Section: Urea Nmentioning
confidence: 99%